A kind of organosilicon modified polymer material and its preparation method and application
By introducing organic silicon and boron nanomium nano -slices in polyurethane materials to prepare modified polyurethane materials, solve the problem of water resistance, thermal stability, and insufficient conductivity of polyurethane materials, and realize the water resistance, thermal stability, conductive electrical conductivity of the material The comprehensive improvement of sexual, self -repair, and flame retardant performance.
Patent Information
- Application Number
- CN202411140700.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-08-20
AI Technical Summary
The existing polyurethane materials have poor water resistance, insufficient thermal stability, and lack of electrical conductivity, self-healing and flame retardancy in liquid or humid environments, which limit their use in certain application fields.
By introducing silicone and boron nitride nanosheets, a modified polyurethane material with dynamic reversible disulfide bonds is prepared, and the water resistance, thermal stability and flame retardant properties of the material are improved through cross-linking reaction, while giving the material conductivity and self-propelled properties. Fix performance.
It has achieved a comprehensive improvement in the water resistance, thermal stability, conductivity, self-healing and flame retardant properties of polyurethane materials, broadening its applications in electronic equipment and other fields.
Smart Images

Figure GDA0005174994510000101 
Figure GDA0005174994510000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to an organosilicon-modified polymer material and a preparation method thereof. Background Art
[0002] Polyurethane materials have become one of the most widely used polymer materials in industrial production and daily life due to their excellent mechanical properties. However, polyurethane contains a large number of amine-urethane bonds and urea groups, which leads to poor water resistance of polyurethane materials and makes them unable to work in liquid or humid environments. Higher temperatures will also destroy the physical properties of polyurethane materials. Silicone materials have good water resistance and thermal stability due to the high bond energy of the silicon-oxygen-silicon bond in the main chain. Introducing silicone into polyurethane to obtain silicone-modified polyurethane can combine the advantages of both and improve the thermal stability and water resistance of polyurethane materials.
[0003] Traditional polyurethane materials are usually insulating, which limits their application in some fields that require conductive properties, such as wearable flexible sensors, so it is necessary to prepare conductive polyurethane to broaden its application in these fields; similarly, polyurethane polymer materials will inevitably cause cracks or breaks due to aging or mechanical damage during use, reducing the service life of the material. In order to effectively improve the service life of the material, the material can be given certain self-repairing properties; in addition to self-repairing properties, polyurethane materials with flame retardant properties are also necessary. When encountering high temperature or fire source, the combustion of polyurethane may endanger public safety, and polyurethane materials with flame retardant properties can improve safety to a certain extent; the silicone-modified polymer material prepared by the present invention has excellent water resistance, self-repairing, flame retardancy and conductivity, and is of great significance in many fields such as electronic equipment. Summary of the invention
[0004] The purpose of the present invention is to provide an organosilicon modified polymer material and a preparation method and application thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing an organosilicon-modified polymer material comprises the following preparation steps:
[0007] (1) 1,2-bis(2-bromoethyl)disulfide, allylamine, potassium carbonate and tetrahydrofuran are uniformly mixed in a mass ratio of 1:(1.3-1.5):(3.5-4.5):(6-8), stirred at 30-40° C. for 10-12 h, filtered and the filtrate is retained, and the filtrate is rotary evaporated at 40-50° C. and 2.66 kPa for 20-30 min to obtain a diene monomer;
[0008] (2) Weigh the following components: isophorone diisocyanate, polypropylene glycol, dibutyltin dilaurate, N-methylpyrrolidone-tetrahydrofuran solution, diene monomer, 1,4-butanediol, mix isophorone diisocyanate, polypropylene glycol, dibutyltin dilaurate and N-methylpyrrolidone-tetrahydrofuran solution evenly, heat to 70-80° C., react for 2-3 h to obtain a polyurethane prepolymer, then add the diene monomer and continue to react for 2-3 h, then add 1,4-butanediol and stir for 30 min, pour into a polytetrafluoroethylene mold, and dry in a vacuum oven at 80° C. for 72 h to obtain a modified polyurethane;
[0009] (3) mixing carboxylated boron nitride nanosheets, N,N'-dicyclohexylcarbodiimide and 3-aminomethylthiophene in a mass ratio of 1:(5-6):(100-120), ultrasonically dispersing for 30-40 min, heating to 120° C. and stirring for 24-26 h at a stirring speed of 400-500 r / min. After the reaction is completed, filtering and washing with anhydrous ethanol for 3-4 times, and drying at 60° C. for 20-22 h to obtain thienyl boron nitride nanosheets;
[0010] (4) Mixing thiophene boron nitride nanosheets, thiophene, 3-allylthiophene, polyvinyl pyrrolidone and chloroform in a mass ratio of 1:(3-4):(2-3):(5-6):(50-60), adding anhydrous ferric chloride in an amount of 0.2%-0.3% by mass of the thiophene boron nitride nanosheets, adding ammonium persulfate in an amount of 1%-1.2% by mass of the thiophene boron nitride nanosheets, stirring at a speed of 500-600 r / min for 20-22 h, filtering and washing with chloroform for 3-4 times, washing with pure water for 3-4 times, and drying at 60° C. for 20-22 h to obtain modified boron nitride nanosheets;
[0011] (5) The modified polyurethane, end-containing hydrogen silicone oil, modified boron nitride nanosheets and tetrahydrofuran are mixed in a mass ratio of 1:(2-3):(0.1-0.15):(30-40), ultrasonically dispersed for 60 minutes, 0.1%-0.3% of the mass of the modified polyurethane castable platinum catalyst is added, stirred for 3-5 minutes, poured into a polytetrafluoroethylene mold, and dried in a vacuum oven at 80°C for 48 hours to obtain a silicone modified polymer material.
[0012] As an optimization, the mass fractions of the components in step (2) are: 1 part of isophorone diisocyanate, 17-18 parts of polypropylene glycol, 0.02-0.03 parts of dibutyltin dilaurate, 25-30 parts of N-methylpyrrolidone-tetrahydrofuran solution, 0.7-0.8 parts of diene monomer, and 0.3-0.4 parts of 1,4-butanediol; the molecular weight of the polypropylene glycol is 2000; and the N-methylpyrrolidone-tetrahydrofuran solution is prepared by mixing N-methylpyrrolidone and tetrahydrofuran in a volume ratio of 1:1.
[0013] As an optimization, the particle size of the carboxylated boron nitride nanosheets in step (3) is 500 nm.
[0014] As an optimization, the molecular weight of the terminal hydrogenated silicone oil in step (5) is 8000; the model of the Castaplatin catalyst is KP36.
[0015] The present invention also provides an organosilicon-modified polymer material prepared by the method for preparing the organosilicon-modified polymer material.
[0016] The present invention also provides an application of an organosilicon-modified polymer material prepared by the method for preparing the organosilicon-modified polymer material.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] When preparing the organosilicon modified polymer material, the present invention firstly reacts 1,2-bis(2-bromoethyl) disulfide and propyleneamine to obtain a diene monomer, synthesizes a prepolymer from isophorone diisocyanate and polypropylene glycol, and then uses the diene monomer and 1,4-butanediol as a chain extender to obtain a modified polyurethane; then, a carboxylated boron nitride nanosheet and 3-aminomethylthiophene are reacted to obtain a thienyl boron nitride nanosheet, and thiophene and 3-allylthiophene are polymerized on the surface of the thienyl boron nitride nanosheet to obtain a modified boron nitride nanosheet; and finally, the modified polyurethane, hydrogen-containing silicone oil and the modified boron nitride nanosheet are cross-linked to obtain the organosilicon modified polyurethane material.
[0019] Firstly, 2-bis(2-bromoethyl) disulfide and allylamine are reacted by the nucleophilic substitution reaction of amino group and bromine to obtain a diene monomer, and a disulfide bond is introduced into the structure of the diene monomer. Isophorone diisocyanate and polypropylene glycol are used to synthesize a prepolymer, and then a modified polyurethane is prepared using the diene monomer and 1,4-butanediol as chain extenders. The modified polyurethane main chain contains a dynamically reversible disulfide bond, which can give the polyurethane material self-healing properties.
[0020] Then, carboxylated boron nitride nanosheets and 3-aminomethylthiophene are reacted with amino groups and carboxyl groups to obtain thiophene-based boron nitride nanosheets, and then thiophene and 3-allylthiophene are polymerized on the surface of thiophene-based boron nitride nanosheets to obtain modified boron nitride nanosheets. 3-aminomethylthiophene is connected to the boron nitride nanosheets through covalent bonds, and 3-aminomethylthiophene is polymerized with other thiophene and 3-allylthiophene on the surface of the boron nitride nanosheets to form polythiophene with bromine groups, which enhances the bonding force between polythiophene and boron nitride nanosheets. Polythiophene can also give boron nitride good conductivity. The nano-barrier effect produced by the sheet structure of boron nitride nanosheets can form a solid barrier layer inside the material. This barrier layer can effectively slow down the process of heat transfer and oxygen penetration, thereby preventing the combustion process to a certain extent. Boron nitride also exhibits excellent catalytic carbonization. At high temperatures, boron nitride can catalyze the polymer matrix to form a dense and stable carbon layer, which can further block the transfer of heat and oxygen, giving the polyurethane material good flame retardant properties. The polythiophene on the surface of boron nitride can also give the polyurethane good electrical conductivity.
[0021] Finally, the modified polyurethane, hydrogen-containing silicone oil and modified boron nitride nanosheets are cross-linked to obtain a silicone-modified polyurethane material. The hydrogen-containing silicone oil cross-links the modified polyurethane and boron nitride nanosheets containing double bonds through a hydrosilylation reaction, and a long silicon-oxygen chain is introduced into the polyurethane. Due to the high bond energy of the silicon-oxygen-silicon bond in the main chain, the polyurethane has good water resistance and thermal stability, which can improve the thermal stability and water resistance of the polyurethane material. The modified boron nitride nanosheets participate in cross-linking through double bonds, which can improve the dispersibility of the modified boron nitride nanosheets in the material and give the material flame retardancy. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] The particle size of the carboxylated boron nitride nanosheets used in all the following examples and comparative examples is 500 nm, purchased from Beijing Deke Shimadzu Co., Ltd.; the molecular weight of polypropylene glycol is 2000; the molecular weight of the terminal hydrogen-containing silicone oil is 8000; and the model of the Castaplatin catalyst is KP36.
[0024] Example 1
[0025] A method for preparing an organosilicon-modified polymer material comprises the following preparation steps:
[0026] (1) 1,2-bis(2-bromoethyl)disulfide, allylamine, potassium carbonate and tetrahydrofuran were mixed uniformly in a mass ratio of 1:1.3:3.5:6, stirred at 40° C. for 12 h, filtered and the filtrate was retained, and the filtrate was rotary evaporated at 50° C. and 2.66 kPa for 30 min to obtain a diene monomer;
[0027] (2) Weigh the following components: 1 part of isophorone diisocyanate, 17 parts of polypropylene glycol, 0.02 parts of dibutyltin dilaurate, 25 parts of N-methylpyrrolidone-tetrahydrofuran solution, 0.7 parts of diene monomer, and 0.3 parts of 1,4-butanediol, mix the isophorone diisocyanate, polypropylene glycol, dibutyltin dilaurate and N-methylpyrrolidone-tetrahydrofuran solution evenly, heat to 80° C., react for 3 h to obtain a polyurethane prepolymer, then add the diene monomer and continue to react for 3 h, then add 1,4-butanediol and stir for 30 min, pour into a polytetrafluoroethylene mold, and dry in a vacuum oven at 80° C. for 72 h to obtain a modified polyurethane;
[0028] (3) Carboxylated boron nitride nanosheets, N,N'-dicyclohexylcarbodiimide and 3-aminomethylthiophene were mixed uniformly in a mass ratio of 1:5:100, ultrasonically dispersed for 40 minutes, heated to 120°C and stirred for 26 hours at a stirring speed of 500 r / min. After the reaction was completed, the mixture was filtered and washed with anhydrous ethanol for 4 times, and dried at 60°C for 22 hours to obtain thienyl boron nitride nanosheets;
[0029] (4) Mix thiophene boron nitride nanosheets, thiophene, 3-allylthiophene, polyvinyl pyrrolidone and chloroform in a mass ratio of 1:3:2:5:50, add anhydrous ferric chloride of 0.3% by mass of thiophene boron nitride nanosheets, add ammonium persulfate of 1.2% by mass of thiophene boron nitride nanosheets, stir and react at a speed of 600 r / min for 22 hours, filter and wash with chloroform for 4 times, then wash with pure water for 4 times, and dry at 60°C for 22 hours to obtain modified boron nitride nanosheets;
[0030] (5) The modified polyurethane, end-hydrogenated silicone oil, modified boron nitride nanosheets and tetrahydrofuran were mixed in a mass ratio of 1:2:0.1:30, ultrasonically dispersed for 60 minutes, 0.3% of the mass of the modified polyurethane was added with a castable platinum catalyst, stirred for 5 minutes, poured into a polytetrafluoroethylene mold, and dried in a vacuum oven at 80°C for 48 hours to obtain a silicone modified polymer material.
[0031] Example 2
[0032] A method for preparing an organosilicon-modified polymer material comprises the following preparation steps:
[0033] (1) 1,2-bis(2-bromoethyl) disulfide, allylamine, potassium carbonate and tetrahydrofuran were mixed uniformly in a mass ratio of 1:1.7:3:7, stirred at 35° C. for 11 hours, filtered and the filtrate was retained, and the filtrate was rotary evaporated at 45° C. and 2.66 kPa for 25 minutes to obtain a diene monomer;
[0034] (2) Weigh the following components: 1 part of isophorone diisocyanate, 17.5 parts of polypropylene glycol, 0.025 parts of dibutyltin dilaurate, 27 parts of N-methylpyrrolidone-tetrahydrofuran solution, 0.75 parts of diene monomer, and 0.35 parts of 1,4-butanediol, mix the isophorone diisocyanate, polypropylene glycol, dibutyltin dilaurate and N-methylpyrrolidone-tetrahydrofuran solution evenly, heat to 75° C., react for 2.5 hours to obtain a polyurethane prepolymer, then add the diene monomer and continue to react for 2.5 hours, then add 1,4-butanediol and stir for 30 minutes, pour into a polytetrafluoroethylene mold, and dry in a vacuum oven at 80° C. for 72 hours to obtain a modified polyurethane;
[0035] (3) Carboxylated boron nitride nanosheets, N,N'-dicyclohexylcarbodiimide and 3-aminomethylthiophene were mixed uniformly in a mass ratio of 1:5.5:110, ultrasonically dispersed for 35 minutes, heated to 120°C and stirred for 25 hours at a stirring speed of 450 r / min. After the reaction was completed, filtered and washed with anhydrous ethanol for 3 times, and dried at 60°C for 21 hours to obtain thienyl boron nitride nanosheets;
[0036] (4) Mix thiophene boron nitride nanosheets, thiophene, 3-allylthiophene, polyvinyl pyrrolidone and chloroform in a mass ratio of 1:3.5:2.5:5.5:55, add anhydrous ferric chloride of 0.23% by mass of thiophene boron nitride nanosheets, add ammonium persulfate of 1.1% by mass of thiophene boron nitride nanosheets, stir at a speed of 550 r / min for 21 hours, filter and wash with chloroform for 3 times, wash with pure water for 3 times, and dry at 60°C for 21 hours to obtain modified boron nitride nanosheets;
[0037] (5) The modified polyurethane, end-hydrogenated silicone oil, modified boron nitride nanosheets and tetrahydrofuran were mixed in a mass ratio of 1:2.5:0.14:35, and ultrasonically dispersed for 60 minutes. 0.2% of the mass of the modified polyurethane was added with a castable platinum catalyst, stirred for 4 minutes, poured into a polytetrafluoroethylene mold, and dried in a vacuum oven at 80°C for 48 hours to obtain a silicone modified polymer material.
[0038] Example 3
[0039] A method for preparing an organosilicon-modified polymer material comprises the following preparation steps:
[0040] (1) 1,2-bis(2-bromoethyl) disulfide, allylamine, potassium carbonate and tetrahydrofuran are mixed uniformly in a mass ratio of 1:1.5:4.5:8, stirred at 30° C. for 10 h, filtered and the filtrate is retained, and the filtrate is rotary evaporated at 40° C. and 2.66 kPa for 20 min to obtain a diene monomer;
[0041] (2) Weigh the following components: 1 part of isophorone diisocyanate, 18 parts of polypropylene glycol, 0.03 parts of dibutyltin dilaurate, 30 parts of N-methylpyrrolidone-tetrahydrofuran solution, 0.8 parts of diene monomer, and 0.4 parts of 1,4-butanediol, mix the isophorone diisocyanate, polypropylene glycol, dibutyltin dilaurate and N-methylpyrrolidone-tetrahydrofuran solution evenly, heat to 70° C., react for 2 h to obtain a polyurethane prepolymer, then add the diene monomer and continue to react for 2 h, then add 1,4-butanediol and stir for 30 min, pour into a polytetrafluoroethylene mold, and dry in a vacuum oven at 80° C. for 72 h to obtain a modified polyurethane;
[0042] (3) mixing carboxylated boron nitride nanosheets, N,N'-dicyclohexylcarbodiimide and 3-aminomethylthiophene in a mass ratio of 1:6:120, ultrasonically dispersing for 30 min, heating to 120 ° C and stirring for 24 h, stirring at a speed of 400 r / min, filtering and washing with anhydrous ethanol for 3 times after the reaction, and drying at 60 ° C for 20 h to obtain thienyl boron nitride nanosheets;
[0043] (4) Mix thiophene boron nitride nanosheets, thiophene, 3-allylthiophene, polyvinyl pyrrolidone and chloroform in a mass ratio of 1:4:3:6:60, add anhydrous ferric chloride of 0.3% by mass of thiophene boron nitride nanosheets, add ammonium persulfate of 1% by mass of thiophene boron nitride nanosheets, stir and react at a speed of 500 r / min for 20 hours, filter and wash with chloroform for 3 times, wash with pure water for 3 times, and dry at 60°C for 20 hours to obtain modified boron nitride nanosheets;
[0044] (5) The modified polyurethane, end-hydrogenated silicone oil, modified boron nitride nanosheets and tetrahydrofuran were mixed in a mass ratio of 1:3:0.15:40, ultrasonically dispersed for 60 minutes, 0.1% of the mass of the modified polyurethane was added with a castable platinum catalyst, stirred for 3 minutes, poured into a polytetrafluoroethylene mold, and dried in a vacuum oven at 80°C for 48 hours to obtain a silicone modified polymer material.
[0045] Comparative Example 1
[0046] The difference between the preparation method of the organosilicon modified polymer material in Comparative Example 1 and Example 2 lies in step (2). Step (2) is modified to weigh the following components: 1 part of isophorone diisocyanate, 17.5 parts of polypropylene glycol, 0.025 parts of dibutyltin dilaurate, 27 parts of N-methylpyrrolidone-tetrahydrofuran solution, and 0.35 parts of 1,4-butanediol; isophorone diisocyanate, polypropylene glycol, dibutyltin dilaurate and N-methylpyrrolidone-tetrahydrofuran solution are uniformly mixed, the temperature is raised to 75°C, and the reaction is carried out for 2.5 hours to obtain a polyurethane prepolymer; then 1,4-butanediol is added and stirred for 30 minutes; the mixture is poured into a polytetrafluoroethylene mold, and the mixture is dried in a vacuum oven at 80°C for 72 hours to obtain a modified polyurethane.
[0047] Comparative Example 2
[0048] The difference between the preparation method of the organosilicon modified polymer material in Comparative Example 2 and Example 2 lies in step (5). Step (5) is modified as follows: the modified polyurethane, modified boron nitride nanosheets and tetrahydrofuran are mixed in a mass ratio of 1:2.5:0.14:35, ultrasonically dispersed for 60 minutes, 0.2% of the mass of the modified polyurethane by Castaplatin catalyst is added, stirred for 4 minutes, poured into a polytetrafluoroethylene mold, and dried in a vacuum oven at 80°C for 48 hours to obtain the organosilicon modified polymer material.
[0049] Comparative Example 3
[0050] The difference between the preparation method of the organosilicon modified polymer material in Comparative Example 3 and Example 2 lies in step (5). Step (5) is modified as follows: the modified polyurethane, terminal hydrogen silicone oil and tetrahydrofuran are mixed in a mass ratio of 1:2.5:0.14:35, ultrasonically dispersed for 60 minutes, 0.2% of the mass of the modified polyurethane by Castaplatin catalyst is added, stirred for 4 minutes, poured into a polytetrafluoroethylene mold, and dried in a vacuum oven at 80°C for 48 hours to obtain the organosilicon modified polymer material.
[0051] Comparative Example 4
[0052] The preparation method of the organosilicon modified polymer material in Comparative Example 4 differs from that in Example 2 in that step (4) is not included, and step (5) is modified as follows: modified polyurethane, end-hydrogenated silicone oil, thienyl boron nitride nanosheets and tetrahydrofuran are mixed in a mass ratio of 1:2.5:0.14:35, ultrasonically dispersed for 60 minutes, 0.2% of the mass of the modified polyurethane by Castaplatin catalyst is added, stirred for 4 minutes, poured into a polytetrafluoroethylene mold, and dried in a vacuum oven at 80°C for 48 hours to obtain the organosilicon modified polymer material.
[0053] Test Example 1
[0054] Flame retardant performance test
[0055] Test method: The examples and comparative examples were prepared into standard samples according to GB / T 2048, and the limiting oxygen index of the examples and comparative examples was tested. The results are shown in Table 1.
[0056] Table 1
[0057] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 31.26 Comparative Example 1 31.59 Example 2 31.47 Comparative Example 2 28.36 Example 3 32.54 Comparative Example 3 22.37 Comparative Example 4 32.01
[0058] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the organosilicon modified polymer material prepared in the present invention has good flame retardant properties.
[0059] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Examples 2 to 3, indicating that the carboxylated boron nitride nanosheets and 3-aminomethylthiophene are reacted through amino and carboxyl groups to obtain thiophene-based boron nitride nanosheets, and then thiophene and 3-allylthiophene are polymerized on the surface of thiophene-based boron nitride nanosheets to obtain modified boron nitride nanosheets, 3-aminomethylthiophene is connected to the boron nitride nanosheets through covalent bonds, and 3-aminomethylthiophene is polymerized with other thiophene and 3-allylthiophene on the surface of the boron nitride nanosheets to form polythiophene with bromine groups. , which enhances the bonding force between polythiophene and boron nitride nanosheets; the nano-barrier effect produced by the boron nitride nanosheet structure can form a solid barrier layer inside the material, which can effectively slow down the process of heat transfer and oxygen penetration, thereby preventing the combustion process to a certain extent. Boron nitride also exhibits excellent catalytic carbonization. At high temperatures, boron nitride can catalyze the polymer matrix to form a dense and stable carbon layer, which can further block the transfer of heat and oxygen, giving the polyurethane material good flame retardant properties.
[0060] Test Example 2
[0061] Self-healing performance test
[0062] Test method: All examples and comparative examples were made into specimens according to the standard GB / T 1040.3-2006, and the fracture strength of the specimens was tested at a tensile rate of 50 mm / min, which was recorded as η 0 ; Cut the sample and overlap the cut surface, heat it at 70℃ for 30min, and test the fracture strength of the sample again, which is recorded as η 1 , the self-repair efficiency η is calculated according to the following formula: η=(η 1 / η 0 )*100%. The results are shown in Table 2.
[0063] Table 2
[0064] Self-repair efficiency (%) Self-repair efficiency (%) Example 1 92.41 Comparative Example 1 0 Example 2 90.67 Comparative Example 2 91.47 Example 3 91.11 Comparative Example 3 90.36 Comparative Example 4 91.21
[0065] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the organosilicon-modified polymer material prepared in the present invention has good self-repairing performance.
[0066] By comparison, the self-repairing efficiency of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that a diene monomer is prepared by the nucleophilic substitution reaction of 2-bis(2-bromoethyl)disulfide and acrylamine through amino and bromine, a disulfide bond is also introduced into the structure of the diene monomer, isophorone diisocyanate and polypropylene glycol are used to synthesize a prepolymer, and then a modified polyurethane is prepared using the diene monomer and 1,4-butanediol as a chain extender. The modified polyurethane main chain contains a dynamically reversible disulfide bond, which can give the polyurethane material a self-repairing property.
[0067] Test Example 3
[0068] Water resistance test
[0069] Test method: After all examples and comparative examples were prepared into 2*2 cm squares, the original weight (W 0 ) and immersed in deionized water at room temperature. After 24 h, the sample was taken out and dried naturally and weighed (W 1 ), the water absorption rate is calculated according to the following formula: (W 1 -W 0 ) / W 0 *100%. The results are shown in Table 3.
[0070] Table 3
[0071] Water absorption (%) Water absorption (%) Example 1 1.29 Comparative Example 1 1.30 Example 2 1.32 Comparative Example 2 2.17 Example 3 1.31 Comparative Example 3 1.56 Comparative Example 4 1.47
[0072] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the organosilicon modified polymer material prepared in the present invention has good water resistance.
[0073] By comparison, the water absorption rates of Examples 1 to 3 are lower than that of Comparative Example 2, indicating that the modified polyurethane, hydrogen-containing silicone oil and modified boron nitride nanosheets are cross-linked to prepare the organosilicon-modified polyurethane material, and the hydrogen-containing silicone oil cross-links the modified polyurethane containing double bonds and the boron nitride nanosheets through a silylation reaction, and introduces long silicon-oxygen chains into the polyurethane. Due to the high bond energy of the silicon-oxygen-silicon bond in the main chain, the polyurethane has good water resistance and thermal stability, and can improve the water resistance of the polyurethane material.
[0074] Test Example 4
[0075] Conductivity test
[0076] Test method: All examples and comparative examples were prepared into 1*1mm samples, and square resistance was tested using RTS-9 dual-electric four-probe tester with a current of 1mA and a range of 10-4 Ω-10 6 The results are shown in Table 4.
[0077] Table 4
[0078]
[0079]
[0080] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 4, it can be found that the organosilicon-modified polymer material prepared in the present invention has good electrical conductivity.
[0081] By comparison, the square resistance of Examples 1 to 3 is smaller than that of Comparative Examples 3 to 4, indicating that thiophene-based boron nitride nanosheets are prepared by reacting carboxylated boron nitride nanosheets and 3-aminomethylthiophene through the reaction of amino and carboxyl groups, and then thiophene and 3-allylthiophene are polymerized on the surface of thiophene-based boron nitride nanosheets to prepare modified boron nitride nanosheets, 3-aminomethylthiophene is connected to the boron nitride nanosheets through covalent bonds, and 3-aminomethylthiophene is polymerized with other thiophene and 3-allylthiophene on the surface of the boron nitride nanosheets to form polythiophene with bromine groups, thereby enhancing the bonding force between polythiophene and the boron nitride nanosheets. Polythiophene can also give boron nitride good conductivity, thereby giving the polyurethane material good conductivity.
[0082] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an organosilicon-modified polymer material, characterized in that: The method comprises the following preparation steps: (1) 1,2-bis(2-bromoethyl)disulfide, allylamine, potassium carbonate and tetrahydrofuran are mixed uniformly in a mass ratio of 1:(1.3-1.5):(3.5-4.5):(6-8), stirred at 30-40°C for 10-12h, filtered and the filtrate is retained, and the filtrate is rotary evaporated at 40-50°C and 2.66kPa for 20-30min to obtain a diene monomer; (2) Weigh the following components: isophorone diisocyanate, polypropylene glycol, dibutyltin dilaurate, N-methylpyrrolidone-tetrahydrofuran solution, diene monomer, 1,4-butanediol, mix isophorone diisocyanate, polypropylene glycol, dibutyltin dilaurate and N-methylpyrrolidone-tetrahydrofuran solution evenly, heat to 70-80°C, react for 2-3 hours to obtain a polyurethane prepolymer, then add the diene monomer and continue to react for 2-3 hours, then add 1,4-butanediol and stir for 30 minutes, pour into a polytetrafluoroethylene mold, and dry in a vacuum oven at 80°C for 72 hours to obtain a modified polyurethane; (3) Mix carboxylated boron nitride nanosheets, N,N'-dicyclohexylcarbodiimide and 3-aminomethylthiophene in a mass ratio of 1:(5-6):(100-120), perform ultrasonic dispersion for 30-40 min, heat to 120 °C and stir for 24-26 h, stir at 400-500 r / min, filter after the reaction, wash with anhydrous ethanol 3-4 times, and dry at 60 °C for 20-22 h to obtain thienyl boron nitride nanosheets; (4) Mix thiophene boron nitride nanosheets, thiophene, 3-allylthiophene, polyvinyl pyrrolidone and chloroform in a mass ratio of 1:(3-4):(2-3):(5-6):(50-60), add 0.2%-0.3% of anhydrous ferric chloride by mass of the thiophene boron nitride nanosheets, add 1%-1.2% of ammonium persulfate by mass of the thiophene boron nitride nanosheets, stir at a speed of 500-600 r / min for 20-22 h, filter and wash with chloroform for 3-4 times, then wash with pure water for 3-4 times, and dry at 60°C for 20-22 h to obtain modified boron nitride nanosheets; (5) The modified polyurethane, end-containing hydrogen silicone oil, modified boron nitride nanosheets and tetrahydrofuran are mixed in a mass ratio of 1:(2-3):(0.1-0.15):(30-40), and ultrasonically dispersed for 60 min. 0.1%-0.3% of the mass of the modified polyurethane castable platinum catalyst is added, stirred for 3-5 min, poured into a polytetrafluoroethylene mold, and dried in a vacuum oven at 80°C for 48 h to obtain a silicone modified polymer material.
2. The method for preparing an organosilicon-modified polymer material according to claim 1, characterized in that: The weight proportions of the components in step (2) are: 1 part of isophorone diisocyanate, 17-18 parts of polypropylene glycol, 0.02-0.03 parts of dibutyltin dilaurate, 25-30 parts of N-methylpyrrolidone-tetrahydrofuran solution, 0.7-0.8 parts of diene monomer, and 0.3-0.4 parts of 1,4-butanediol; the molecular weight of the polypropylene glycol is 2000; the N-methylpyrrolidone-tetrahydrofuran solution is prepared by mixing N-methylpyrrolidone and tetrahydrofuran in a volume ratio of 1:
1.
3. The method for preparing an organosilicon-modified polymer material according to claim 1, characterized in that: The particle size of the carboxylated boron nitride nanosheets in step (3) is 500 nm.
4. The method for preparing an organosilicon-modified polymer material according to claim 1, characterized in that: The molecular weight of the hydrogen-terminated silicone oil in step (5) is 8000; the model of the Castaplatin catalyst is KP36.
5. An organosilicon-modified polymer material prepared according to the method for preparing an organosilicon-modified polymer material according to any one of claims 1 to 4.
6. Use of an organosilicon-modified polymer material prepared by the method for preparing an organosilicon-modified polymer material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Polysiloxanes modified polyurethane for drillable sand-screening pipe, and its preparation method and application
CN102199345A
Method for synthesizing organosilicon modified polyurethane
CN102532478A